â Pengaruh Jenis Infrastruktur, Besaran Anggaran dan Kualitas Infrastruktur terhadap Tingkat Kepuasan Masyarakat - Indra Krisnadi; Nuraini Asriati (Syntax Idea)
The presence of the State financial balance law gives local governments authority over the finances provided by the central government to be managed properly. One of the local government budgets is intended for various developments. The infrastructure development is aimed at the welfare of the community which ends in community satisfaction. The research design used is a quantitative design with a survey approach. The population in this study were all people in Kubu Raya District. The sampling technique is random sampling. So that the sample used in the study was 78 people in Kubu Raya Regency who were randomly selected. Data was collected through questionnaires distributed to respondents. The data that has been collected is then analyzed using the help of the SPSS statistical program. The results showed that the type of infrastructure, budget size, and infrastructure quality affect the level of community satisfaction.